Improved joint health in subjects with severe haemophilia A treated prophylactically with recombinant factor VIII Fc fusion protein. Issue 1 (30th October 2017) - Oldenburg, J.; Kulkarni, R.; Srivastava, A.; Mahlangu, J. N.; Blanchette, V. S.; Tsao, E.; Winding, B.; Dumont, J.; Jain, N.
Abstract : Introduction: Joint arthropathy is the long‐term consequence of joint bleeding in people with severe haemophilia. Aim: This study assessed change in joint health over time in subjects receiving recombinant factor VIII Fc fusion protein (rFVIIIFc) prophylaxis. Methods: ALONG is the phase 3 pivotal study in which the benefit of rFVIIIFc as a prophylactic treatment for bleeding control was shown in previously treated severe haemophilia patients ≥12 years of age (arm 1: 25‐65 IU/kg every 3‐5 days, arm 2: 65 IU/kg weekly and arm 3: episodic). After completing ALONG, subjects had the option to enrol into the extension study (ASPIRE). This interim, post hoc analysis assessed changes in joint health over ~2.8 years in these patients. Results: Forty‐seven subjects had modified Haemophilia Joint Health Score (mHJHS) data at A‐LONG baseline, ASPIRE baseline and ASPIRE Year 1 and Year 2. Compared with A‐LONG baseline (23.4), mean improvement at ASPIRE Year 2 was −4.1 (95% confidence interval [CI], −6.5, −1.8; P  =   .001). Regardless of prestudy treatment regimen, subjects showed continuous improvement in mHJHS from A‐LONG baseline through ASPIRE Year 2 (prestudy prophylaxis: −2.4, P  =   .09; prestudy episodic treatment: −7.2, P  =   .003). Benefits were seen in subjects with target joints (−5.6, P  = .005) as well as those with severe arthropathy (−8.8, P  = .02). The mHJHS components with the greatest improvement at ASPIRE Year 2 were swelling (−1.4, P  =   .008), range of motion (−1.1, P  =   .03) and strength (−0.8, P =  .04). Conclusions: Prophylaxis with rFVIIIFc may improve joint health over time regardless of prestudy prophylaxis or episodic treatment regimens.